2016
DOI: 10.1109/tnb.2016.2631240
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Delay Spread in Multilayer Diffusion-Based Molecular Communication (DBMC) Channel

Abstract: In nanoscale communication, diffusion-based molecular communication (DBMC) in which information is encoded into molecule patterns by a transmitter nanomachine, has emerged as a promising communication system, particularly for biomedical and healthcare applications. Although, numerous studies have been conducted to evaluate and analyze DBMC systems, investigation on DBMC system through a multilayer channel has received less attention. The aims of this paper are to formulate channel characteristics and to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The peak time increases because the molecules will take longer time to reach the RN. When average diffusion coefficient for multilayer diffusion is employed [11]- [12], we can observe the larger deviation of the received signal from the actual received signal derived analytically for a three-layer MCvD medium. This shows that the averaging approach can"t predict the amplitude and time characteristics of the molecular received signal accurately in a multilayer MCvD medium .…”
Section: Numerical and Simulation Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The peak time increases because the molecules will take longer time to reach the RN. When average diffusion coefficient for multilayer diffusion is employed [11]- [12], we can observe the larger deviation of the received signal from the actual received signal derived analytically for a three-layer MCvD medium. This shows that the averaging approach can"t predict the amplitude and time characteristics of the molecular received signal accurately in a multilayer MCvD medium .…”
Section: Numerical and Simulation Resultsmentioning
confidence: 85%
“…Moreover, it is shown that the effective averaging approach for multilayer medium available in the literature [11]- [12] fails to model the multilayer molecular communication environment accurately. The proposed model has important applications in biomedical engineering, particularly, in the design of future targeted drug delivery system where it can be used for predicting the actual drug concentration around the target site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a lot of research has been carried out in the context of DMC. As some examples, when assuming that the transmitter, receiver or both employ channel knowledge, the capacity of different DMC channels has been investigated [18][19][20][21][22]. In terms of signalling, DMC may make use of molecular concentration to form concentration shift keying (CSK) [18,[23][24][25][26][27], of molecular pulse positions to yield pulse position modulation (PPM) [28], and of molecular types to allow molecularshift keying (MoSK) [24,29,30], which constitute the three basic modulation schemes for information transmission in DMC.…”
Section: Introductionmentioning
confidence: 99%
“…However, this work examined the performance of different estimators for a homogeneous medium of single diffusion coefficient without providing any insight M about modelling a multiple-region medium. Recently, in the literature, the channel impulse response (CIR), delay spread etc., have been derived for a MCvD medium with multiple regions with different diffusion properties by replacing it with an equivalent homogeneous medium having a single region with an effective diffusion properties [19]- [20]. The effective (average) diffusion coefficient is derived in [19]- [20] by averaging the diffusion coefficients of all the multiple regions.…”
Section: Introductionmentioning
confidence: 99%